The Effects of Acute Aerobic Exercise on Blood Pressure, Arterial Function, and Heart Rate Variability in Men Living With HIV - Barros, Juliana Pereira; de Paula, Tainah; Mediano, Mauro Felippe Felix; Rangel, Marcus Vinicius dos Santos; Monteiro, Walace; Cunha, Felipe Amorim da; Farinatti, Paulo; Borges, Juliana Pereira (Frontiers in Physiology, 2021)
Purpose: To investigate the effects of acute cycling on blood pressure (BP), arterial function, and heart rate variability (HRV) in men living with HIV (MLHIV) using combined antiretroviral therapy (cART). Methods: Twelve MLHIV (48.7±9.2 y; 25.2±2.8 kg/m2) and 13 healthy controls (41.2±9.9 y; 26.3±2.9 kg/m2) performed a cycling bout (ES) (intensity: 50% oxygen uptake reserve; duration: time to achieve 150 kcal - MLHIV: 24.1±5.5 vs. Controls: 23.1±3.0 min; p=0.45), and a 20-min non-exercise session (NES). Results: At rest (p<0.05), MLHIV presented higher brachial systolic/diastolic BP (SBP/DBP: 123.2±14.2/76.8±6.3 vs. 114.3±5.1/71.6±2.6 mmHg), and central BP (cSBP/cDBP: 108.3±9.3/76.5±6.5 vs. 101.6±4.9/71.3±4.4 mmHg) vs. Controls, but lower absolute maximal oxygen uptake (2.1±0.5 vs. 2.5±0.3 L.min-1) and HRV indices reflecting overall/vagal modulation (SDNN: 24.8±7.1 vs. 42.9±21.3 ms; rMSSD: 20.5±8.5 vs. 38.1±22.8 ms; pNN50: 3.6±4.2 vs. 13.6±11.3 %). DBP postexercise lowered in Controls vs. MLHIV (~4 mmHg, p<0.001; ES: 0.6). Moreover, Controls vs. MLHIV had greater reductions (p < 0.05) in augmentation index (-13.6 ± 13.7 vs. -3.1 ± 7.2 %/min; ES: 2.4), and HRV indices up to 5-min (rMSSD: -111.8±32.1 vs. -75.9±22.2 ms/min; ES: 3.8; pNN50: -76.3±28.3 vs. -19.0±13.7 %/min; ES: 4.4). Within-group (ES vs. NES; p<0.05) reductions occurred in Controls for SBP (~10 mmHg, 2 h), DBP (~6 mmHg, 20, 30, 70 min), cSBP (~9 mmHg, 30 min), cDBP (~7 mmHg, 30, 70 min), augmentation index (~10%, 30 min), and pNN50 (~20%; up to 2 h), while in MLHIV only cSBP (~6 mmHg, 70 min) and cDBP (~4 mmHg, 30 min) decreased. Similar increases (up to 5 min) in heart rate (~22 bpm), and decreases in SDNN (~18 ms) and rMSSD (~20 ms) occurred in both groups. Conclusion: MLHIV under cART exhibited attenuated post-exercise hypotension vs. healthy controls, which seemed to relate with impairments in vascular function.